2018
DOI: 10.21608/jhiph.2018.19916
|View full text |Cite
|
Sign up to set email alerts
|

Awareness of Married Adults about Congenital Anomalies in a Rural Village, Assiut

Abstract: Background: Congenital anomalies (CA) are significant causes of infant morbidity, mortality and disability. Objective(s): To assess the knowledge and attitude regarding congenital anomalies and their associated factors among married adults. Methods: A community based cross sectional study was conducted on 633 currently married inhabitants in a rural village, Assiut. An interview was used for data collection via a semi-structured questionnaire. Results: Most participants (96.7%) had ever heard about CA, 20.1% o… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 8 publications
0
1
0
Order By: Relevance
“…Effective cooperation between parents and health care professionals such as doctors, nurses, speech therapists, and occupational therapists will increase the parents' knowledge resulting in a low incidence of complications from children's congenital anomalies and promoting overall child health. Faddan and Ismail ( 21 ) suggested that a health education program is very crucial, particularly the role of healthcare providers in counseling and raising awareness among parents regarding congenital anomalies. Dingemann et al ( 22 ) revealed that low maternal education correlated with a higher risk of complications among the children following surgeries for their congenital anomalies.…”
Section: Discussionmentioning
confidence: 99%
“…Effective cooperation between parents and health care professionals such as doctors, nurses, speech therapists, and occupational therapists will increase the parents' knowledge resulting in a low incidence of complications from children's congenital anomalies and promoting overall child health. Faddan and Ismail ( 21 ) suggested that a health education program is very crucial, particularly the role of healthcare providers in counseling and raising awareness among parents regarding congenital anomalies. Dingemann et al ( 22 ) revealed that low maternal education correlated with a higher risk of complications among the children following surgeries for their congenital anomalies.…”
Section: Discussionmentioning
confidence: 99%